(Invited) Broadband Spectroscopic Characterization of Electrically Active Defects in Dielectrics: Monitoring the in-Service Evolution of Dialectics in Integrated System. (26th April 2016) - Obeng, Yaw S.; Okoro, Chukwudi A; Amoah, Papa K.; You, Lin
Abstract : Emerging nanoelectronics are been hindered by reliability challenges such as stress related failures. The chemistry and physics of the materials play crucial roles in the changes in the reliability over time, especially in low operating voltage devices which are fabricated using low temperatures processes. The low-temperature-processed materials are metastable due to the presence of reactive metastable intermediates from the precursors, and incomplete reactions within the films that result in electrically active defects in the "as deposited" films. Metrology is thus needed for the accurate quantification of the reliability impact of these defects in integrated systems. In this paper, we discuss the use of broadband microwave to detect, characterize and monitor the evolution of active defect in low-temperature processed dielectric films under simulated use conditions. The impact of thermal exposure on the behavior of electrical defects shed light on the chemical changes occurring within the dielectric films during use.